NEW PUBLIC SERVICE PARADIGM IN FISIP INSTITUTION OF MUHAMMADIYAH UNIVERSITY JAKARTA - Muhtadin, Imam; Qudrat Nugraha, Muhammad; Sanjaya, Makroen; Satiadarmanto, Deddi Fasmadhy (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
This research is to find out alternative strategies for improving the quality of institutional services for lecturers and education staff at FISIP Muhammadiyah University Jakarta with the principle of New Public Service in institutional services for lecturers and education staff. The background of public service literature is fundamentally humanistic (citizens do not serve customers), where the public interest (seeking the public interest) and accountability for the Implementation of New Public Services are prioritized on the principle of being able to increase the synergy of public services and the responsiveness of public service organizations to the needs of lecturers and education staff in FISIP Muhammadiyah University Jakarta, applying the citizen model does not serve customers, strives for public interest and public service accountability as part of the New Public Service principle as an alternative to improving the quality of public services. The service process for FISIP lecturers and education staff at the University of Muhammadiyah Jakarta is a process of interdependence between the actors involved and bargaining occurs between actors.